The cognitive effects of an acute wild blueberry intervention on 7- to 10-year-olds using extended memory and executive function task batteries. Issue 5 (19th May 2020) - Whyte, Adrian R.; Lamport, Daniel J.; Schafer, Graham; Williams, Claire M.
Abstract : In two separate experiments, children were tested on memory and executive function task batteries. Shorter memory reaction times were observed on the visuo-spatial grid task and short executive function times were observed on congruent trials of the attention network task. Abstract : Evidence for the health benefits of blueberries is well documented. In particular, memory and executive function benefits have both been found for children aged 7–10 in the 6 hours period following acute blueberry consumption. Previous research has utilised a limited number of tasks when considering these domains. Therefore, in two separate experiments, we employed extended memory and executive function task batteries to further understand the extent of blueberry benefits. Following blueberry intervention, children aged 7–10 were tested on a memory battery at 75 minutes and an executive function battery at 3 hours. Shorter memory reaction times were observed on the visuo-spatial grid task and shorter executive function reaction times were observed on the congruent trials of the attention network task. Whilst providing further evidence for the cognitive benefits of blueberry consumption in school age children, these findings contrast with previous research where improved accuracy and reaction time benefits have most commonly been found on more cognitively demanding trials. Further research targeted to consider the areas of the brain related to each cognitive domain and how they coincide with mechanisms of action, such as increases in cerebral blood flow following blueberry intervention, is therefore recommended.